Manganase superoxide dismutase polymorphism in chronic pelvic pain syndrome patients - Arısan, Serdar; Kiremit, Murat Can; Tığlı, H.; Çaşkurlu, T.; Ünsal, Zeynep Narçin; Ergenekon, E.; ARISAN, ELİF DAMLA (My University, 2006)
Chronic pelvic pain syndrome (CPPS) is a common and serious health problem affecting the quality of life in men. In this study, we aim to investigate the manganase superoxide dismutase (MnSOD) polymorphism at nucleotide 47 as a result of the change of Ala to Val on the protein sequence in CPPS patients. The frequencies were 0.45 and 0.38 for the Ala and 0.55 and 0.62 for Val in National Institutes of Health category 3a and 3b groups. The differences between control and CPPS patients were statistically significant (P<0.05). However, frequencies recorded in 3a and 3b groups were not statistically different (P>0.05). Same results were obtained for enzyme analysis of MnSOD and glutathione peroxidase. Control group antioxidant enzyme levels were higher than patients' samples. The low antioxidant status of CPPS patients might be the clue for pathophysiological problems, and highly distributed Val allele frequency can be a mediator point of the illness. Our findings lead to the suggestion that oxidative disorder-linked medical health problems can be associated with genetic risk factors such as polymorphisms.